THE EFFECT OF TWO STAY TWO STRAY (TSTS) METHOD ON RECOUNT TEXT WRITING AT THE EIGHTH GRADE STUDENTS OF SMPN 2 SAWAHAN - Devi Apriliawati; Lulus Irawati; Erlik Widiyani Styati (English Teaching Journal : A Journal of English Literature, Language and Education, 2017)
This research is conducted to explain about the Effect of Two Stay Two Stray (TSTS) Method on Recount text Writing. The objectives of this research are to describe the effect of two tay two stray (TSTS) method on recount text writing at eighth grade students of SMPN 2 Sawahan. The sample of this research are 8-A consisted of 21 students in the eighth grade of SMPN 2 Sawahan. The research approach that is used in this study is quantitative. The research was conducted by using experiment. The technique that is used in this research is paired sample T-test that has pre-test and post-test. The result of this research shows that Two Stay Two Stray (TSTS) Method gives significant effect to the students’ writing ability in recount text. It can be seen from the value of t  is -8,840 with significant value 0,000. It shows that the probabilities value of students’ writing ability is lower than 0,05 (0,000<0,05) level of significant. So, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. It can be stated that there is a significant different of students’ writing ability before being taught using Two Stay Two Stray (TSTS) Method and after being taught using Two Stay Two Stray (TSTS) Method. The conclusion of this research is Two Stay Two Stray (TSTS) Method help the students to increase their achievement in writing recount text and this method also has possitive effect on students’ writing ability especially on recount text.